Competing for Capital: Auditing and Credibility in Financial Reporting - Raphael Boleslavsky; Bruce Ian Carlin; Christopher Cotton (Queen's University, Department of Economics, 2017)
When self-interested agents compete for scarce resources, they often exaggerate the promise of their activities. As such, principals must consider both the quality of each opportunity and each agent's credibility. We show that principals are better off with less transparency because they gain access to better investments. This is due to a complementarity between the agents' effort provision and their ability to exaggerate. As such, it is suboptimal for principals to prevent misreporting, even if doing so is costless. This helps explain why exaggeration is ubiquitous during allocation decisions: money management, analyst coverage, private equity fundraising, and venture capital investments.
Keywords: D83; G14; G31; 330; Auditing; Monitoring; Financial Reporting; Capital Budgeting; Exaggeration; Rechnungswesen; Projektbewertung; Investitionsrechnung; Prinzipal-Agent-Theorie